Macroeconomic modeling of regional economies: A useful tool or a mere intellectual game? - Zaleski, Janusz (Journal of Public Governance, 2011)
The aim of the paper is to assess the validity of application of macroeconomic modeling at the regional level – both as a tool of counterfactual impact analysis of financial intervention and of a forecast method of socio-economic trends. The reasoning is based on the results of the regional HERMIN models contrasted critically with other macroeconomic simulations on the regional level. The author concludes that it is justified to construct relatively simple and robust econometric models of regional economies, and that, for their application, it is necessary to have in-depth empirical knowledge of the regional economy under consideration.